2023
DOI: 10.1111/cns.14130
|View full text |Cite
|
Sign up to set email alerts
|

Srs11‐92, a ferrostatin‐1 analog, improves oxidative stress and neuroinflammation via Nrf2 signal following cerebral ischemia/reperfusion injury

Abstract: Aim Ferroptosis is increasingly becoming to be considered as an important mechanism of pathological cell death during stroke, and specific exogenous ferroptosis inhibitors have the ability to reverse cerebral ischemia/reperfusion injury. However, research on Srs11‐92 (AA9), a ferrostatin‐1 (Fer‐1) analog, in preclinical studies is limited. Methods In the middle cerebral artery occlusion‐reperfusion (MCAO/R) mice model or oxygen–glucose deprivation/reperfusion (OGD/R) ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…The academic community has been devoted to exploring various neuroprotective strategies after neuronal injury ( 29 31 ). In present work, we found significant differences in gut microbiota composition (including a high level of A. muciniphila ) in male Pgam5 -/- mice compared to male WT mice.…”
Section: Discussionmentioning
confidence: 99%
“…The academic community has been devoted to exploring various neuroprotective strategies after neuronal injury ( 29 31 ). In present work, we found significant differences in gut microbiota composition (including a high level of A. muciniphila ) in male Pgam5 -/- mice compared to male WT mice.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the inflammatory response after cerebral infarction can exacerbate oxidative stress. 28–30 The inflammatory response will lead to the infiltration and chemotaxis of a large number of inflammatory cells, which will release a large amount of reactive oxygen species and inflammatory factors, further aggravating cell damage and death. We found that the increase in SDH and ROS immunoreactivity in microglial cells after MCAO compared to the control samples was reversed by treatment with F-Mito.…”
Section: Discussionmentioning
confidence: 99%
“…The sepsis rat model was established via intraperitoneal injection of 5 mg/kg LPS [ 12 ], followed by intravenous injection of remimazolam (10 mg/kg; Jiangsu; China) [ 8 ] or 0.9% saline. Notably, α7nAChR agonist (PNU282987, 10 mg/kg, Sigma, USA) [ 13 ], Nrf2/HO-1 inhibitor (ML385, 30 mg/kg, Selleck, USA) [ 14 ], and α7nAChR antagonist (MLA, 3 mg/kg, abcam) [ 15 ] were dissolved in normal saline with 2% DMSO and administered intraperitoneally 30 min before LPS treatment. The SDV or Sham rats underwent surgery two weeks before modeling.…”
Section: Methodsmentioning
confidence: 99%